2021
DOI: 10.54156/cbe.bej.10.1.236
|View full text |Cite
|
Sign up to set email alerts
|

Emperical Analysis of the Quality Infrastructure in Trade Facilitation Within the African Continental Free Trade

Abstract: This study mainly focused on exploring the roles of standardisation and quality infrastructure systems in aiding trade and sustainable development within the African continental free trade area. This is a conceptual study. It was established that facilitating trade and sustainable development lead to attaining economic growth of any developing country. Several factors are involved in facilitating trade and sustainable development, including quality infrastructure and standardisation. These two factors foster f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…These findings align with Mangula's (2013) study that reported that the product quality in TMIs had been meaningly upgraded due to the adoption and being certified by ISO 9001. Quality is a distinctive characteristic or attribute possessed by a product or service (Nzumile and Taifa, 2019, 2021a, 2021b); it thus has to be achieved excellently (Taifa et al. , 2021b).…”
Section: Resultsmentioning
confidence: 99%
“…These findings align with Mangula's (2013) study that reported that the product quality in TMIs had been meaningly upgraded due to the adoption and being certified by ISO 9001. Quality is a distinctive characteristic or attribute possessed by a product or service (Nzumile and Taifa, 2019, 2021a, 2021b); it thus has to be achieved excellently (Taifa et al. , 2021b).…”
Section: Resultsmentioning
confidence: 99%
“…Quality can be defined in several ways; this study considered it as the fitness for use or the degree of excellence for a process, system, service or product (Nzumile and Taifa, 2019, 2021). Figure 2 portrays the EFQM 2020 model as an updated business model that incorporates Industry 4.0 elements and contributes to the Quality 4.0 concepts (Fonseca et al.…”
Section: Theoretical Orientationmentioning
confidence: 99%
“…Quality can be defined as a degree of excellence (Nzumile and Taifa, 2019, 2021), and quality improvement fosters profit increase (Taifa et al. , 2021b).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The first industrial revolution featured mechanical manufacturing and distinguished the first factory system through equipment employment, initially driven by foot treadles, shortly after by steam or water (Gokalp et al, 2017;Taifa et al, 2020). The second industrial revolution combined science and mass manufacturing from the late nineteenth to the early twentieth centuries (Figure 1) (Gokalp et al, 2017;Taifa et al, 2020Taifa et al, , 2021. It was a period of electricity, fast standardisation and production lines.…”
Section: Theoretical Background 21 the Fourth Industrial Revolutionmentioning
confidence: 99%